Assessment of Frailty Scores Among Geriatric Patients Hospitalized in the North-Western Region of Romania: A Cross-Sectional Study - Lucreția Avram; Marius I. Ungureanu; Dana Crişan; Valer Donca (Medicina)
Background and Objectives: The global demographic trend of population aging is evident across all regions, with a notable increase in the proportion of elderly individuals. Romania exemplifies this phenomenon, as 17% of its population is currently aged 65 years or older—a figure projected to rise to 25% by 2050. This demographic shift underscores the pressing need for comprehensive measures to address the health and social requirements of this growing population segment. This study aims to assess the prevalence of frailty among older adults in Romania and explore its relationship with socioeconomic factors. Materials and Methods: We employed a quantitative approach, by using cross-sectional data from patients hospitalized at the geriatrics ward of the Municipal Clinical Hospital in Cluj-Napoca, Romania. Frailty scores were calculated through established frailty assessment tools, allowing for a comprehensive evaluation of frailty status. In addition, we compared the socioeconomic characteristics of frail and non-frail patients to identify potential disparities. Statistical analyses were performed to assess associations between frailty and socioeconomic factors, providing insight into the relationship between these variables within the patient population. Results: The prevalence of frailty in our sample is, depending on the frailty scale used, 55% to 79%, which is in line with figures from specialized geriatric wards in other studies. There is moderate to substantial agreement between the scales we compared, and all six scales seem to concurrently agree on the frailty diagnostic in 55% of cases. Additionally, frail patients are more likely to have a low socioeconomic status. Conclusions: A significant limitation in European frailty research has been the absence of comparative frailty prevalence data across several European countries, especially those with lower economic development. Our study fills this gap by providing data on frailty prevalence in the north-western region of Romania.